PENGARUH STIMULASI KUTANEUS SLOW STROKE BACK MASSAGE TERHADAP INTENSITAS NYERI HAID (DISMENORE) PADA REMAJA - Dewi, Purnama (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Menstruation is the periodic and cyclic bleeding from the uterus accompanied the release of the endometrium. At the time of menstruation, women usually have physical and mental complaints, one of them is painful menstruation (dysmenorrhea). Dysmenorrhea is painful stiffness or spasms in the lower abdomen, hips, and lower back that before or during menstruation. There are two types of therapy to treat dysmenorrhea are pharmacological and non-pharmacological therapy. Ofne of non pharmacological that can be used is the cutaneous stimulation slow strokes back massage. This research aimed to know the effect of cutaneous stimulation slow stroke back massage on intensity of painful menstruation in teenagers in SMA Negeri 1 Dawan. The type of research is a pre-experimental research design with one group pretest-posttest. Sampling was done by purposive sampling as many as 30 people. The results of this study found that the average respondent pain scale before given cutaneous stimulation slow stroke back massage was 6.37 and the average pain scale after the respondent was given cutaneous stimulation of slow stroke back massage was 3.13. The results of statistical tests with wilcoxon (p ? 0.05) obtained the value of sig. (2-tailed) 0.000 which mean that the cutaneous stimulation slow stroke back massage intervention significantly affect on intensity of painful menstruation in teenagers in SMA Negeri 1 Dawan. By knowing the benefits and effects of cutaneous stimulation slow strokes back massage to decrease the intensity of painful mentruation (dysmenorrhea) is expected from  the school especially coach infirmary in order to provide information to the students in preventing and overcoming the painful menstruation (dysmenorrhea) at the time of menstruation.
Keywords: Cutaneous Stimulation Slow Stroke Back Massage; Painful menstruation (Dysmenorrhea).